2014
DOI: 10.1111/evo.12554
|View full text |Cite
|
Sign up to set email alerts
|

Fitness decline in spontaneous mutation accumulation lines ofCaenorhabditis eleganswith varying effective population sizes

Abstract: The rate and fitness effects of new mutations have been investigated by mutation accumulation (MA) experiments in which organisms are maintained at a constant minimal population size to facilitate the accumulation of mutations with minimal efficacy of selection. We evolved 35 MA lines of Caenorhabditis elegans in parallel for 409 generations at three population sizes (N = 1, 10, and 100), representing the first spontaneous long-term MA experiment at varying population sizes with corresponding differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(96 citation statements)
references
References 51 publications
9
85
2
Order By: Relevance
“…Indeed, we found that nearly all the variation in fitness among segregants from diploid and haploid lines was explained by one or two large-effect mutations, which implies that variance in fitness among lines is largely due to variance in mutational effects. This is expected when lines are propagated for a short period of time (Wloch et al 2001) but is perhaps more surprising in long-term lines such as Dickinson's [although for similar results, see also Caballero et al (2002), Halligan et al (2003), Estes et al (2004), Heilbron et al (2014), and Katju et al (2015)]. …”
Section: Discussionmentioning
confidence: 74%
“…Indeed, we found that nearly all the variation in fitness among segregants from diploid and haploid lines was explained by one or two large-effect mutations, which implies that variance in fitness among lines is largely due to variance in mutational effects. This is expected when lines are propagated for a short period of time (Wloch et al 2001) but is perhaps more surprising in long-term lines such as Dickinson's [although for similar results, see also Caballero et al (2002), Halligan et al (2003), Estes et al (2004), Heilbron et al (2014), and Katju et al (2015)]. …”
Section: Discussionmentioning
confidence: 74%
“…Although worms cannot match the short generation times or large population sizes of microbes such as yeast or bacteria commonly employed for EE ( b ell 1997; k assen 2014), relatively long-term evolution is feasible with C. elegans ; e.g. , lineages have been cultured under selfing for up to 400 generations ( m atsuba et al 2012; k atju et al 2015), and maintained under different reproductive systems for up to 200 generations ( t heologidis et al 2014). …”
Section: What Is Experimental Evolution?mentioning
confidence: 99%
“…Left, illustration of how an MA experiment is performed, adapted from Halligan and Keightley (2009) and Katju et al (2015). G indicates the generation of EE, N the number of individuals allowed to reproduce within each MA line, and n the number of MA lines.…”
Section: Goals Outcomes and Interpretation Of Experimental Evolutionmentioning
confidence: 99%
“…These lineages accumulate mutations independently over several thousand generations, and the magnitude and variance in fitness between lineages can be used to estimate several properties of the distribution of fitness effects (Halligan and Keightley 2009). MA studies have been used to characterize the fitness effects of spontaneous mutations in Drosophila melanogaster (Bateman 1959;Mukai 1964;Keightley 1994;Fry et al 1999), Arabidopsis thaliana Shaw et al 2000Shaw et al , 2002, Caenorhabditis elegans (Keightley and Caballero 1997;Vassilieva et al 2000;Estes et al 2004;Katju et al 2015), Saccharomyces cerevisiae (Wloch et al 2001;Zeyl and de Visser 2001;Dickinson 2008;Jasmin and Lenormand 2015), Escherichia coli (Kibota and Lynch 1996;Trindade et al 2010), and other microbes (Heilbron et al 2014;Kraemer et al 2015). Results from these studies have occasionally been inconsistent, but the majority of results suggest that most spontaneous mutations have mild effects (Eyre-Walker and Keightley 2007;Halligan and Keightley 2009;Agrawal and Whitlock 2012;Heilbron et al 2014), that deleterious mutations far outnumber beneficial mutations (Keightley and Lynch 2003;Eyre-Walker and Keightley 2007;Silander et al 2007), and that the distribution of effects of deleterious mutations is complex and multimodal (Zeyl and de Visser 2001;Eyre-Walker and Keightley 2007).…”
mentioning
confidence: 99%